Sodium ion battery positive electrode sheet and preparation method thereof, sodium ion battery and preparation method thereof, and electrical equipment

By using the structure of a functional primer layer and an active material layer in the positive electrode sheet of the sodium ion battery, the problems of low compaction density and large internal contact resistance of the polyanionic material are solved, and the electrochemical performance is improved.

CN119764333APending Publication Date: 2025-04-04深圳为方能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963760.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The compaction density of existing polyanionic materials in sodium ion batteries is low, and the internal resistance of contact with conventional aluminum foils is large, affecting electrochemical properties.

Method used

A sodium ion battery positive electrode sheet structure is adopted that includes a base material, a functional primer layer and an active material layer. A conductive agent, a binder, a sodium supplement agent and a solvent are added to the functional primer layer, and a binder, a conductive agent and a positive electrode active material are added to the active material layer. The positive electrode sheet is prepared by coating and drying.

Benefits of technology

The conductivity of the active substance is improved, the compaction of the material electrode sheet is increased, the peel strength of the active substance layer is increased, the compaction of the polyanionic material and the internal contact resistance are improved, and the electrochemical performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764333A_ABST
    Figure CN119764333A_ABST
Patent Text Reader

Abstract

The present application provides a sodium ion battery positive electrode sheet and a preparation method thereof, a sodium ion battery and a preparation method thereof, and electrical equipment, and relates to the field of new energy technology. The sodium ion battery positive electrode sheet of the present application includes a substrate, a functional bottom coating, and an active material layer. The functional bottom coating is first coated on the substrate, and then the active material layer is coated on the functional bottom coating, which can increase the conductivity of the active material, increase the compaction of the material electrode sheet, increase the peeling strength of the active material layer, and improve the low compaction and large contact internal resistance of the polyanion material. A sodium supplement is added to the functional bottom coating, and the sodium supplement releases a large amount of sodium ions when it is first activated, resulting in an increase in the irreversible capacity of the battery cell; the sodium supplement not only decomposes without residue after the first charge activation, but also does not affect the conductivity of the bottom coating, and the gas generated during the first activation plays a pore-forming role in the active material layer, increases the ion transmission channel, enhances the wettability of the electrolyte, reduces the static infiltration time of the battery cell, and improves the rate performance of the battery cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a sodium ion battery positive electrode sheet and a preparation method thereof, a sodium ion battery and a preparation method thereof, and electrical equipment. Background Art

[0002] As the penetration rate of new energy power generation increases, the randomness and volatility of the power generation side are becoming increasingly severe. As a new source of regulation capacity, energy storage has accelerated the demand for installed capacity. Compared with lithium-ion batteries, industrialized sodium-ion batteries have obvious cost advantages. In addition, the safety performance, high and low temperature performance, and rate performance of sodium-ion batteries are better than those of lithium-ion batteries, and are expected to become an important supplement to energy storage.

[0003] Among the three major routes for sodium-ion battery cathodes, polyanion compounds have stable structures, high cycle life, high thermal stability, and high operating voltage, making them the most suitable route for long-term energy storage. However, polyanion materials have poor processing performance, and the material has a large contact internal resistance with conventional aluminum foil, which affects the electrochemical performance of sodium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a sodium ion battery positive electrode sheet and a preparation method thereof, a sodium ion battery and a preparation method thereof, and electrical equipment, aiming to solve the problem that the existing polyanion material has low compaction density and large contact internal resistance with conventional aluminum foil.

[0005] To achieve the above objectives, the present application provides a sodium ion battery positive electrode sheet, please refer to Figure 1 , comprising: a substrate, a functional primer layer disposed on both sides of the substrate, and an active material layer disposed on the functional primer layer;

[0006] The raw materials of the functional bottom coating layer include: a binder, a conductive agent, a sodium supplement and a solvent; the raw materials of the active material layer include: a binder, a conductive agent, a positive electrode active material and a solvent.

[0007] In some embodiments, the raw materials of the functional primer layer include, by weight: 0.8-2 parts of a binder, 15-30 parts of a conductive agent, 0.5-4 parts of a sodium supplement, and 44-85 parts of a solvent; the binder can be, for example, 0.8 parts, 1 part, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, or any value between 0.8-2 parts; the conductive agent can be, for example, 15 parts, 17 parts, 20 parts, 22 parts, 25 parts, 28 parts , 30 parts or any value between 15-30 parts; the sodium supplement can be, for example, 0.5 parts, 0.8 parts, 1 part, 1.3 parts, 1.5 parts, 2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or any value between 0.5-4 parts; the solvent can be, for example, 44 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts or any value between 44-85 parts.

[0008] In some embodiments, the raw materials of the active material layer include, by weight: 4-10 parts of a binder, 2-6 parts of a conductive agent, and 84-94 parts of a positive electrode active material, and the solvent adjusts the solid content to 50%. The binder may be, for example, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, or any value between 4-10 parts; the conductive agent may be, for example, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, or any value between 2-6 parts; the positive electrode active material may be, for example, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, or any value between 84-94 parts.

[0009] Optionally, the thickness of the substrate is 12-16 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or any value between 12-16 μm;

[0010] Optionally, the thickness of the functional primer layer is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between 1-5 μm;

[0011] Optionally, the thickness of the active material layer is 30-120 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm or any value between 30-120 μm.

[0012] In some embodiments, at least one of the following conditions is met:

[0013] A. The substrate is selected from any one of aluminum foil, aluminum mesh, and PET composite aluminum foil;

[0014] Optionally, the substrate is aluminum foil;

[0015] B. The binder is selected from one or two of polyvinylidene fluoride, polytetrafluoroethylene, (vinylidene fluoride-hexafluoroethylene), poly(vinylidene fluoride-hexafluoropropylene), polymethyl acrylate, and acrylamide-acrylic acid polymer;

[0016] Optionally, the binder is polyvinylidene fluoride;

[0017] C. The conductive agent is selected from one or more of carbon black, carbon nanotubes, graphene, and conductive graphite;

[0018] Optionally, the conductive agent includes carbon black and conductive graphite;

[0019] D. the sodium supplement is selected from sodium oxalate;

[0020] E. the solvent is selected from deionized water or N-methylpyrrolidone;

[0021] Optionally, the solvent is N-methylpyrrolidone;

[0022] F. The positive electrode active material is selected from a polyanion compound, the chemical formula of which is Na n [Mn x Fe y Ni z Li 1-x-y-z ]O2, where 0.8≤n<0.84, 0.5≤x<0.6, 0.08≤y≤0.15, 0.18≤z, 3.47≤x / z≤4.66;

[0023] G. The particle size of the positive electrode active material is Dv50≤6 μm.

[0024] The present application also provides a method for preparing the above-mentioned sodium ion battery positive electrode sheet, comprising:

[0025] Coating a functional primer solution on both sides of a substrate to obtain a functional substrate;

[0026] Active material slurry is coated on both sides of the functional substrate, and then dried to obtain the sodium ion battery positive electrode sheet.

[0027] In some embodiments, at least one of the following conditions is met:

[0028] A. The coating method includes any one of spraying, roller coating, and gravure printing;

[0029] Optionally, the coating method is spraying;

[0030] B. The drying temperature is 70°C-95°C.

[0031] The present application also provides a sodium ion battery, the raw materials of which include the above-mentioned sodium ion battery positive electrode sheet.

[0032] The present application also provides a method for preparing the sodium ion battery as described above, comprising:

[0033] Assembling the sodium ion battery positive electrode sheet and negative electrode sheet, a separator and an electrolyte into a battery cell;

[0034] Activating the battery cell by slow gradient charging with a small current to obtain a battery cell activated for the first time;

[0035] The first activated battery cell is evacuated, liquid is replenished, and packaged to obtain the sodium ion battery.

[0036] In some embodiments, the current range of the small current slow gradient charging activation is 0.05C-0.1C, the time is 8-10 hours, and the temperature range is 45°C-60°C.

[0037] In some embodiments, the small current slow gradient charging activation includes: at a temperature of 45° C., using a constant current of 0.05C for 6 hours and a constant current of 0.1C for 4 hours.

[0038] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0039] Compared with the prior art, the beneficial effects of this application include:

[0040] The sodium ion battery positive electrode provided by the present application includes a substrate, a functional bottom coating, and an active material layer. The functional bottom coating is first coated on the substrate, and then the active material layer is coated on the functional bottom coating, which can increase the conductivity of the active material, increase the compaction of the material pole piece, increase the peeling strength of the active material layer, and improve the low compaction of the polyanion material and the large contact internal resistance. A sodium supplement is added to the functional bottom coating. Since the sodium supplement releases a large amount of sodium ions when it is first activated, the irreversible capacity of the battery cell increases, and the sodium ions consumed during film formation are supplemented; the sodium supplement additive used not only decomposes without residue after the first charge activation, but also does not affect the conductivity of the bottom coating, and the gas generated during the first activation plays a pore-forming role on the active material layer of the positive electrode sheet, increases the ion transmission channel, enhances the wettability of the electrolyte, reduces the static infiltration time of the battery cell, and improves the rate performance of the battery cell.

[0041] The sodium ion battery and electrical equipment provided in the present application adopt the sodium ion battery positive electrode sheet of the present application and have excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0043] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet of the sodium ion battery of the present application. DETAILED DESCRIPTION

[0044] As used herein:

[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0046] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0047] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0048] In these examples, parts and percentages are by mass unless otherwise indicated.

[0049] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0050] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0051] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0052] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0053] Example 1

[0054] This embodiment provides a sodium ion battery positive electrode sheet, and the preparation method thereof comprises the following steps:

[0055] a. Add the conductive agent, binder, sodium supplement and solvent in proportion and mix them evenly in a star stirrer to prepare a functional primer liquid; wherein, the conductive agent is a compound of carbon black and conductive graphite (mass ratio 6:4), accounting for 22 parts; the binder is PVDF, accounting for 1.2 parts; the sodium supplement is sodium oxalate (Na2C2O4), accounting for 2 parts; the solvent is NMP, accounting for 74.8 parts; the stirring time is controlled to be 210min, the stirring paddle (rotation) speed is 30rpm, the dispersion disk (revolution) speed is 3000rpm, and the temperature is controlled at 28°C.

[0056] b. The functional primer obtained in step a is evenly coated on both sides of the aluminum foil by a continuous coating process to obtain a functional substrate for standby use; the coating method can be spraying, roller coating, gravure printing, etc., preferably spraying process.

[0057] c. Mix Na4Fe3(PO4)2P2O7, a conductive agent and a binder, add an appropriate amount of an organic solvent, stir evenly, and obtain a mixed slurry; the binder is polyvinylidene fluoride (PVDF), the conductive agent is Ketjen black compounded with graphene (mass ratio 7:3); the organic solvent is NMP; the main material accounts for 94 parts, PVDF accounts for 4 parts, and the conductive agent of carbon black compounded with graphene accounts for 2 parts in total. NMP is used to adjust the solid content and control the solid content at 50%.

[0058] d. The slurry prepared in step c is evenly coated on both sides of the functional substrate prepared in step b, and dried at 85° C. to obtain the sodium ion battery positive electrode sheet of Example 1.

[0059] This embodiment also provides a sodium ion battery, the preparation method of which comprises the following steps:

[0060] e. The sodium ion battery positive electrode sheet of Example 1 is rolled and cut into pieces, and assembled with a hard carbon negative electrode sheet and a PP separator into a semi-finished sodium ion battery.

[0061] f. The semi-finished sodium ion battery obtained in step e is activated by slow gradient charging with a small current (at a temperature of 45°C, a constant current of 0.05C is used for charging for 6 hours, and a constant current of 0.1C is used for charging for 4 hours), and charging is stopped after the sodium supplement is completely reacted, and the gas generated by the reaction is discharged, and secondary packaging is performed to obtain a finished sodium ion battery.

[0062] Example 2

[0063] The difference between Example 2 and Example 1 is that in step a, the conductive agent of carbon black and conductive graphite compound accounts for 22 parts, PVDF accounts for 1.2 parts, sodium oxalate (Na2C2O4) accounts for 3.5 parts, and NMP accounts for 73.3 parts; the other steps and parameters are the same as those in Example 1.

[0064] Example 3

[0065] The difference between Example 3 and Example 1 is that in step a, the conductive agent of the compound of carbon black and conductive graphite accounts for 22 parts, PVDF accounts for 1.2 parts, sodium oxalate (Na2C2O4) accounts for 0.8 parts, and NMP accounts for 76 parts; the other steps and parameters are the same as those in Example 1.

[0066] Example 4

[0067] The difference between Example 4 and Example 1 is that the polyanion material in step c is replaced by a P2-type layered oxide positive electrode material Na 2 / 3 [Ni 1 / 3 Mn 2 / 3 ]O2; other steps and parameters are the same as those in Example 1.

[0068] Comparative Example 1

[0069] The difference between Comparative Example 1 and Example 1 is that in step a, the conductive agent of the compound of carbon black and conductive graphite accounts for 22 parts, PVDF accounts for 1.2 parts, NMP accounts for 76.8 parts, and the functional primer does not add sodium oxalate, a sodium supplement; the other steps and parameters are the same as those in Example 1.

[0070] Comparative Example 2

[0071] The difference between Comparative Example 2 and Example 1 is that the mixed slurry obtained in step c is directly coated on both sides of the aluminum foil, and then the functional primer liquid obtained in step a is coated on the active material layers on both sides; the other steps and parameters are the same as those in Example 1.

[0072] Comparative Example 3

[0073] The difference between Comparative Example 3 and Example 1 is that the mixed slurry obtained in step c is directly coated on both sides of the aluminum foil, and the coating of the functional primer liquid is removed. The other steps and parameters are the same as those in Example 1.

[0074] Comparative Example 4

[0075] The difference between Comparative Example 4 and Example 1 is that in step b, the functional primer liquid of step a is only applied to one side of the aluminum foil, and the primer liquid without adding sodium supplement agent is applied to the other side. The other steps and parameters are the same as those of Example 1.

[0076] Comparative Example 5

[0077] The difference between Comparative Example 5 and Example 4 is that in step a, the conductive agent of the compound of carbon black and conductive graphite accounts for 22 parts, PVDF accounts for 1.2 parts, and NMP accounts for 76.8 parts; the other steps and parameters are the same as those in Example 4.

[0078] Comparative Example 6

[0079] The difference between Comparative Example 6 and Example 4 is that the mixed slurry obtained in step c is directly coated on both sides of the aluminum foil, and the coating of the functional primer liquid is removed; in contrast, the P2 layered oxide does not increase the influence of the functional primer on processing and electrical properties.

[0080] Comparative Example 7

[0081] The difference between Comparative Example 7 and Example 1 is that the sodium supplementer in step a is removed and evenly coated on both sides of the aluminum foil, and then the mixed slurry obtained in step c is coated on both sides of the primer, and finally the functional primer liquid in step a is reconfigured and the functional primer liquid is coated on the active material layers on both sides; the other steps and parameters are the same as those in Example 1.

[0082] The positive electrode sheets of the sodium ion batteries of the embodiments and comparative examples were tested for the porosity of the front and back surfaces (mercury intrusion method), and the first effect (first discharge capacity / first charge capacity, current of 0.2C (1C is 300mA / g), charge and discharge temperature of 25°C) and the proportion of liquid loss (1-liquid retention amount / liquid injection amount) and the internal resistance of the battery cell of the sodium ion batteries of the embodiments and comparative examples were tested. The results are shown in Table 1.

[0083] Table 1. Test results of sodium ion batteries and positive electrodes of various embodiments and comparative examples

[0084]

[0085] According to Table 1, the porosity of the positive and negative surfaces of the positive electrode sheets of the sodium ion batteries of Examples 1 to 4 of the present application is higher than that of the positive electrode sheets of the sodium ion batteries of the comparative example, and the first efficiency of the sodium ion batteries of Examples 1 to 4 is higher than that of the sodium ion batteries of the comparative example. This is because adding a primer layer to the substrate can increase the conductivity of the active material, increase the compaction of the material electrode sheet, and increase the peeling strength of the active material layer; adding a sodium supplement to the primer can increase the irreversible capacity and replenish the sodium ions consumed during film formation; the sodium supplement additive used not only decomposes without residue after the first charge activation, and does not affect the conductivity of the primer, but also the gas generated during the first activation plays a pore-forming role in the active material layer of the positive electrode sheet, increases the ion transmission channel, enhances the wettability of the electrolyte, reduces the static infiltration time of the battery cell, and improves the rate performance of the battery cell.

[0086] In Example 2, the dosage of the sodium supplement agent is increased on the basis of Example 1. The positive electrode sheet of the sodium ion battery has a higher porosity on both sides, a lower liquid loss, a lower internal resistance of the battery cell, and a higher first efficiency, indicating that increasing the sodium supplement agent can produce more gas, have a better pore-forming effect, and provide more sodium ions.

[0087] In Example 3, the dosage of the sodium supplement is reduced on the basis of Example 1, and the indicators of each project are reduced compared with Examples 1 and 2.

[0088] The sodium ion battery positive electrode of Comparative Example 1 has a bottom coating but no sodium supplement, and cannot play the role of electrode pore formation and sodium supplement, so its porosity is lower, the liquid loss is higher, the internal resistance of the battery cell is higher, and the initial efficiency is lower.

[0089] The scheme of Comparative Example 2 swaps the positions of the sodium-supplemented base coating and the active material layer on the electrode. However, due to the particle size and physical and chemical properties such as BET of the polyanion material, the adhesion between the active material layer and the aluminum foil is insufficient under this scheme, resulting in the separation of the active material layer and the aluminum foil during rolling. The experiment is NG.

[0090] The solution of comparative example 3 has no primer layer, and the bonding strength between the active material layer and the aluminum foil is insufficient, resulting in the separation of the active material layer and the aluminum foil during rolling, and the experiment is NG.

[0091] In Comparative Example 4, the electrode is supplemented with sodium on one side, and there is an obvious difference in porosity on both sides of the electrode. Although the first efficiency and rate performance are lower than those in Example 1, they are better than those in Comparative Example 1.

[0092] Compared with Example 4, in Comparative Example 5, the bottom coating layer is not sodium-supplemented, resulting in a lower electrode porosity, an increased internal resistance of the battery cell, and its electrolyte wettability and first efficiency are lower than those of Example 4.

[0093] Comparative Example 6 is compared with Example 4 without a sodium-supplementing primer layer, and is compared with Comparative Example 5 without a primer layer. According to Comparative Example 6, although the P2 layered oxide material can be directly coated on the aluminum foil, coating it on a foil with a functional primer layer can reduce the membrane resistance. The various performances of Comparative Example 6 are lower than those of Example 4; its porosity and electrolyte wettability are consistent with those of Comparative Example 5, indicating that the sodium-supplementing agent has a better pore-forming effect after reaction, and its first effect is lower than that of Comparative Example 5, indicating that the primer can reduce the polarization performance of the battery cell.

[0094] Comparative Example 7 is compared with Example 1. The sodium-supplemented bottom coating and the active material layer on the electrode are swapped, and an additional bottom coating is added to improve the adhesion. According to the data, there is no improvement in the electrode porosity and electrode wettability, and the liquid loss is also higher than that of Example 1. The first efficiency is lower than that of Example 1, but higher than that of Comparative Example 1, but the internal resistance of the battery cell increases significantly.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0096] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A sodium ion battery positive electrode sheet, characterized in that: include: A substrate, a functional primer layer disposed on both sides of the substrate, and an active material layer disposed on the functional primer layer; The raw materials of the functional bottom coating layer include: a binder, a conductive agent, a sodium supplement and a solvent; the raw materials of the active material layer include: a binder, a conductive agent, a positive electrode active material and a solvent.

2. The sodium ion battery positive electrode sheet according to claim 1, characterized in that: The raw materials of the functional primer layer include, by weight: 0.8-2 parts of a binder, 15-30 parts of a conductive agent, 0.5-4 parts of a sodium supplement, and 44-85 parts of a solvent; The raw materials of the active material layer include, by weight: 4-10 parts of a binder, 2-6 parts of a conductive agent and 84-94 parts of a positive electrode active material, and the solvent is adjusted to a solid content of 50%; Optionally, the thickness of the substrate is 12-16 μm; Optionally, the thickness of the functional primer layer is 1-5 μm; Optionally, the active material layer has a thickness of 30-120 μm.

3. The sodium ion battery positive electrode sheet according to claim 1 or 2, characterized in that: At least one of the following conditions is met: A. The substrate is selected from any one of aluminum foil, aluminum mesh, and PET composite aluminum foil; Optionally, the substrate is aluminum foil; B. The binder is selected from one or two of polyvinylidene fluoride, polytetrafluoroethylene, (vinylidene fluoride-hexafluoroethylene), poly(vinylidene fluoride-hexafluoropropylene), polymethyl acrylate, and acrylamide-acrylic acid polymer; Optionally, the binder is polyvinylidene fluoride; C. The conductive agent is selected from one or more of carbon black, carbon nanotubes, graphene, and conductive graphite; Optionally, the conductive agent includes carbon black and conductive graphite; D. the sodium supplement is selected from sodium oxalate; E. the solvent is selected from deionized water or N-methylpyrrolidone; Optionally, the solvent is N-methylpyrrolidone; F. The positive electrode active material is selected from a polyanion compound, the chemical formula of which is Na n [Mn x Fe y Ni z Li 1-x-y-z ]O2, where 0.8≤n<0.84, 0.5≤x<0.6, 0.08≤y≤0.15, 0.18≤z, 3.47≤x / z≤4.66; G. The particle size of the positive electrode active material is Dv50≤6 μm.

4. A method for preparing a positive electrode sheet for a sodium ion battery according to any one of claims 1 to 3, characterized in that: include: Coating a functional primer solution on both sides of a substrate to obtain a functional substrate; Active material slurry is coated on both sides of the functional substrate, and then dried to obtain the sodium ion battery positive electrode sheet.

5. The method for preparing a positive electrode sheet for a sodium ion battery according to claim 4, characterized in that: At least one of the following conditions is met: A. The coating method includes any one of spraying, roller coating, and gravure printing; Optionally, the coating method is spraying; B. The drying temperature is 70°C-95°C.

6. A sodium ion battery, characterized in that: The raw materials include the sodium ion battery positive electrode sheet according to any one of claims 1 to 3.

7. A method for preparing a sodium ion battery as claimed in claim 6, characterized in that: include: Assembling the sodium ion battery positive electrode sheet and negative electrode sheet, a separator and an electrolyte into a battery cell; Activating the battery cell by slow gradient charging with a small current to obtain a battery cell activated for the first time; The first activated battery cell is evacuated, liquid is replenished, and packaged to obtain the sodium ion battery.

8. The method for preparing a sodium ion battery according to claim 7, characterized in that: The current range of the small current slow gradient charging activation is 0.05C-0.1C, the time is 8-10 hours, and the temperature range is 45°C-60°C.

9. The method for preparing a sodium ion battery according to claim 8, characterized in that: The small current slow gradient charging activation includes: at a temperature of 45° C., using a constant current of 0.05C for 6 hours and a constant current of 0.1C for 4 hours.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 6.